2008
DOI: 10.1104/pp.107.112789
|View full text |Cite
|
Sign up to set email alerts
|

A Novel WRKY Transcription Factor Is Required for Induction of PR-1a Gene Expression by Salicylic Acid and Bacterial Elicitors  

Abstract: PR-1a is a salicylic acid-inducible defense gene of tobacco (Nicotiana tabacum). One-hybrid screens identified a novel tobacco WRKY transcription factor (NtWRKY12) with specific binding sites in the PR-1a promoter at positions 2564 (box WK 1 ) and 2859 (box WK 2 ). NtWRKY12 belongs to the class of transcription factors in which the WRKY sequence is followed by a GKK rather than a GQK sequence. The binding sequence of NtWRKY12 (WK box TTTTCCAC) deviated significantly from the consensus sequence (W box TTGAC[C/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(163 citation statements)
references
References 52 publications
7
146
0
1
Order By: Relevance
“…However, several studies have revealed that some WRKY proteins can bind to non-W or non-W-like box ciselements (Sun et al, 2003;Cai et al, 2008;van Verk et al, 2008). For example, a Suc-regulated barley (Hordeum vulgare) WRKY transcription factor, SUGAR SIG-NALING IN BARLEY2, can bind to both the W box and a sugar-responsive element (Sun et al, 2003).…”
Section: Wrky13 Specifically Binds To Multiple Types Of Cis-elements mentioning
confidence: 99%
“…However, several studies have revealed that some WRKY proteins can bind to non-W or non-W-like box ciselements (Sun et al, 2003;Cai et al, 2008;van Verk et al, 2008). For example, a Suc-regulated barley (Hordeum vulgare) WRKY transcription factor, SUGAR SIG-NALING IN BARLEY2, can bind to both the W box and a sugar-responsive element (Sun et al, 2003).…”
Section: Wrky13 Specifically Binds To Multiple Types Of Cis-elements mentioning
confidence: 99%
“…5). Previous studies have reported that a barley (Hordeum vulgare) WRKY protein binds to a sugarresponsive cis-element specifically and a tobacco (Nicotiana tabacum) WRKY binds to a WK-box (Sun et al, 2003;van Verk et al, 2008). Thus, further study is required to determine whether OsWRKY13 could regulate OsWRKY45-1 via binding to a non-W-box or non-W-box-like element.…”
Section: Oswrky45 and Oswrky13 May Regulate Each Other In A Feedback mentioning
confidence: 99%
“…Members of this family contain at least one conserved DNA-binding region, designated the WRKY domain, comprising the highly conserved WRKYGQK peptide sequence and a zinc finger motif (CX 4-7 CX 22-23 HXH/C). This domain generally binds to the DNA element termed the W box (C/TTGACT/C), although alternative binding sites have been identified (Sun et al, 2003;Cai et al, 2008;Ciolkowski et al, 2008;van Verk et al, 2008). WRKY family members are divided into three groups based on the number of WRKY domains and certain features of the zinc finger-like motifs (Eulgem et al, 2000).…”
Section: The Wrky Factorsmentioning
confidence: 99%